The Personal Imapact of Ethical Decisiosn: A Social Penetration Theory - Baack, Donald (Journal of business ethics, 2000)
There are gaps in the Social and Ethical issues literature regarding the structure of individual ethical reasoning and the process through which personal ethical standards erode or decline. Social Penetration Theory may be used to view ethical issues of low, moderate, or high salience. It also produces a model of the process by which an individual turns to less desirable ethical reasoning and behavior.